2022
DOI: 10.3390/polym14091647
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Biomass Derived Adsorbents for Co(II) Remediation, Recycling and Analysis

Abstract: The gradual replacement of conventional materials with materials tailored to the green development goals is one of the needs of the day. Correspondingly, this article reviews and integrates, for the first time, the gathered knowledge on the use of the adsorbents based on polymeric biomasses (biosorbents) for a cleaner separation of cobalt (Co) from synthetic and actual solutions. It is a two-part comprehensive approach that debates the Co biosorption potential of bio-based polymers from the perspective of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…It was observed that the biosorbents presented a good affinity for the metal cations, for a contact time of 120 min, especially the 250 µm fraction that allowed one to remove between 11.80 and 32.50% of As, 11.17 and 34.10% of Cd, and 12.23 and 36.30% of Zn, Pb being the one that presented the greatest removal between 90.70 and 96.14%, similar to values reported by various authors, using different lignocellulosic materials [ 50 , 51 , 52 , 53 ]. On the other hand, the mixed treatment presented better heavy metal adsorption capacity, which would be related to the acid treatment that eliminated hemicellulose and the basic treatment that removed lignin, obtaining biosorbents rich in cellulose, a fundamental component in the processes of metal cation removal [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the biosorbents presented a good affinity for the metal cations, for a contact time of 120 min, especially the 250 µm fraction that allowed one to remove between 11.80 and 32.50% of As, 11.17 and 34.10% of Cd, and 12.23 and 36.30% of Zn, Pb being the one that presented the greatest removal between 90.70 and 96.14%, similar to values reported by various authors, using different lignocellulosic materials [ 50 , 51 , 52 , 53 ]. On the other hand, the mixed treatment presented better heavy metal adsorption capacity, which would be related to the acid treatment that eliminated hemicellulose and the basic treatment that removed lignin, obtaining biosorbents rich in cellulose, a fundamental component in the processes of metal cation removal [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The better removal of the 250 µm fraction was due to the greater contact surface that the biosorbents had during the sorption process, additionally enhanced by the fact that they were treated sequentially with sulfuric acid and sodium hydroxide, which caused the removal of hemicellulose and lignin, respectively [ 54 , 55 ]. Similar results were reported by several authors for pretreated biomasses rich in lignocellulosic components [ 41 , 42 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reusing the adsorbent is one of the important criteria for application of the adsorbent in water and wastewater adsorptive industries (Koopal et al 2019;Tofan 2022). Thus, selection of stable bio-adsorbent has viable advantages for re-utilization of used adsorbents for new adsorption phase after several adsorption-desorption cycles (dos Santos et al 2019;Alaqarbeh 2021).…”
Section: Reusability Of Scb Adsorbentsmentioning
confidence: 99%
“…However, RHB has a poor adsorption capacity for specific metal ions in a polymetallic solution [ 13 , 117 ]. A study investigated the adsorption effectiveness of 21 types of biochar in polymetallic solutions.…”
Section: Rice Husk Biochar As An Adsorbentmentioning
confidence: 99%